Inflammation in osteonecrosis of the femoral head: Evaluation of hematological biomarkers and potential prognostic value - Tran Canh Tung Nguyen; Dao Doan Trinh Phan; Thi Huyen Do; Thanh Nam Luong; Hoang Khang Le (PLoS ONE, 2026)
Increasing evidence suggests that inflammation and immune imbalance are associated with osteonecrosis of the femoral head (ONFH). This study aimed to investigate peripheral inflammatory biomarkers in patients with nontraumatic ONFH and assess their potential prognostic value. A retrospective analysis was conducted on 80 patients with nontraumatic ONFH and 110 control individuals without ONFH. Peripheral blood cell counts, C-reactive protein (CRP), and derived inflammatory indices including neutrophil-to-lymphocyte ratio (NLR), monocyte-to-lymphocyte ratio (MLR), platelet-to-lymphocyte ratio (PLR), and systemic immune-inflammation index (SII) were compared between groups and among different disease stages. Diagnostic performance was assessed using receiver operating characteristic (ROC) curve analysis. The results showed that ONFH patients showed significantly higher CRP, monocyte count (cM), monocyte percentage (pM), MLR, and platelet count (PLT). ROC analysis revealed that CRP (AUC = 0.700, sensitivity = 71.3%, specificity = 65.5%) and cM (AUC = 0.690, sensitivity = 82.5%) had the highest diagnostic accuracy. CRP levels differed significantly across disease stages, peaking at stage II (P = 0.0107), while other indices remained stable. These findings support the concept that both systemic and local inflammatory mechanisms contribute to the pathogenesis of ONFH. CRP and monocyte indices may serve as inexpensive, accessible adjuncts for early disease screening and monitoring.